The Colonization and Effect of Isaria cateinannulata on Buckwheat Sprouts - Xiaona Zhang; Xue Peng; Guimin Yang; Qingfu Chen; Daochao Jin (Plants, 2022)
The use of entomogenous fungi as endophytes is currently an area of active research. Isaria cateniannulata is an important entomogenous fungus that has been employed for the active control of a range of pests in agricultural and forestry settings, but its direct impact on plants remains to be evaluated. Herein, we assessed the ability of I. cateniannulata to colonize buckwheat, Fagopyrum esculentum and F. tataricum, and its impact on buckwheat defense enzyme activity and physiological indexes. The majority of fungal submerge condia was able to enter into leaves through stomata and veins, and this was followed by conidial attachment, lytic enzyme secretion, conidial deformation, and enhanced defensive enzyme activity within buckwheat, followed by the repair of damaged tissue structures. I. cateniannulata populations on buckwheat leaf surfaces (in CFU/g) reached the minimum values at 24 h after inoculation. At this time, the blast analysis revealed that the sequence identity values were 100%, which was consistent with the sequence of I. cateniannula. The number of I. cateniannulata submerge conidia colonized in the buckwheat leaves gradually rose to peak levels on 7 d post-inoculation, and then gradually declined until 10 d, at which time the buckwheat plant growth index values increased. This study provided novel evidence that I. cateniannulata could be leveraged as an endophytic fungus capable of colonizing buckwheat plants and promoting their growth.